PEMBENTUKAN NILAI RAPOR MELALUI NILAI TUGAS DAN NILAI ULANGAN - Nur Samsiah, (Pendidikan Ekonomi, 2012)
The achievement report of a student must consider the students task assessment and daily examinations. The study, therefore, is intended to find out (1) whether the task assessment and daily examination contribute integratedly to composing the achievement report of accounting subject of the eleventh grade students of social science at SMA Hang Tuah 2 Sidoarjo, (2) whether task assessment and daily examinations discreetly contribute to the achievement reporting, (3) which of the two variables is the most dominant in contributing to the achievement reporting. The study uses descriptive qualitative approach. The data were collected through interview and documentation. The data then were analized with double linier regression analysis. The study shows that(1) there is asignificant influence of varieble X1 and X2 integratedly on the achievement reporting, which is 36.013, (2) there is also significant influence of X1 and X2  discreetly on the achievement reporting which is up to 5.642, and (3) the most dominant variable is task assessment.